Sustainable magnetic biochar from agro-aquacultural waste for efficient Pb(II) and Cd(II) removal: Machine learning–assisted optimization and techno-economic evaluation - Limmun, Wanida; Limmun, Warunee; Prangmoo, Yasumin; Ishikawa, Nao; Borkowski, John J.; Chungcharoen, Thatchapol; Ito, Ayumi (My University, 2026)
This study presents the sustainable synthesis and optimization of magnetic biochar derived from agro-aquacultural waste, specifically rubber seed shells and oyster shells (MRO), for the efficient removal of Pb(II) and Cd(II) from aqueous solutions. MRO was synthesized via FeCl3 activation and co-pyrolysis, enhancing adsorption capacity and magnetic recoverability. Process optimization was performed using Response Surface Methodology (RSM) and a Genetic Algorithm–Backpropagation Neural Network (GA–BPNN), with experimental validation confirming RSM-predicted conditions. The optimized MRO achieved high adsorption capacities of 709.99 mg/g for Pb(II) and 332.98 mg/g for Cd(II), following Langmuir and pseudo-second-order kinetic models. Mechanistic analysis identified surface complexation, ion exchange, electrostatic interaction, and precipitation as key pathways. MRO demonstrated excellent reusability, maintaining over 90% Pb(II) removal efficiency after 11 regeneration cycles. Techno-economic and environmental assessments revealed a low production cost (23 THB/kg), modest energy consumption (2.5 kWh/kg), and a reduced carbon footprint (0.50 kg CO2/kg). These results underscore the potential of MRO as a cost-effective and scalable adsorbent for sustainable wastewater treatment applications.
Keywords: Agro-aquacultural waste; Machine learning optimization; Magnetic biochar; Pb(II) and Cd(II) removal; Response surface methodology; Techno-economic analysis